EFFECTIVENESS OF MANALAGI MANGGO LEAF EXTRACT GEL (Mangifera indica L.) ON CUTTING WOUND HEALING IN MALE RABBITS NEW ZEALAND WHITE - Luthfiyanti, Niken; Muktamaroh, Anif; Khasanah, Isna Nur (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2023)
Wounds are pathological conditions that occur in skin tissue and mucous membranes of other tissues. Mango leaves (Mangifera indica L.) contain alkaloids, flavonoids, tannins and saponins which have an effect on wound healing. The purpose of this study was to determine the effectiveness of mango leaf extract gel concentration (Mangifera indica L.) on wound healing in rabbits. The test animals were divided into five treatments, namely positive control, negative control, and gel preparation with 3 variations of extract concentration, namely formula I (10%), formula II (15%), and formula III (20%). This research is an experimental study with observations for 14 days. The statistical test uses the Anova test and the Post-Hoc test. The average healing time of the positive control and negative control groups with mango leaf extract gel (Mangifera indica L.) concentrations of 10%, 15%, and 20% had a significant difference with a sig 0.000 result (P<0.05). Manalagi mango leaf extract gel (Mangifera indica L.) provides the best wound healing effect at a concentration of 20%.